Clay Mineralogy and Solution Chemistry of Waterlogged Saline Soil Undergone Subsurface Drainage: Study from North-Western India-Western India: Waterlogged saline soil of North-Western India - Mukhopadhyay, Raj; Saroha, Diksha; Paul, Ranjan; Narjary, Bhaskar; Bundela, Devendra; Kumar, Satyendra; Barman, Arijit (Journal of Soil Salinity and Water Quality, 2024)
Subsurface drainage (SSD) is an effective technique to reclaim waterlogged saline soils and improving agricultural production with added economic returns. In 2019, Sampla (Rohtak, Haryana, India) SSD site was revisited to study the identification and characterization of clay minerals and their transformation in relation to soil solution chemistry under prevailing conditions. The soil was clay loam to clay in texture with high ECe (3.48-4.67 dSm-1) and pHs (8.03-8.06). The 30-60cm soil-depth showed the highest cation exchange capacity (16.25 meq/100g) and exchangeable sodium percentage (8.04%) followed by the surface soils (14.17 meq/100g and 7.65% respectively). The exchangeable calcium (Ca2+) and magnesium (Mg2+) varied between 7.92-9.19 and 3.04-4.20 meq/100g, respectively, the highest being in 30-60cm soil-depth. The soluble cations followed the order Na+ (17.73–24.79 meqL-1) > Ca2++Mg2+ (7.77–11.02 meqL-1) > K+ (5.93–7.61 meqL-1) up to 90cm soil-depth. The soil structural stability ratios, namely, SAR, PAR, MCAR and CROSS, were found maximum (12.37, 3.80, 10.02 and 22.06 respectively) in 30-60 cm soil-depth highlighting greater dispersion, poor soil structure and aggregate stability in the sub-surface. The clay minerals including hydroxy interlayered vermiculite, chlorite and mica were dominant at 0-60 cm, followed by kaolin, quartz, rutile and K Feldspar at deeper soil layer (60-90cm). The soil chemical analysis showed the redevelopment of salinity with the dominance of Na+ ions throughout the profile due to stoppage of SSD operation for a long time. The relative similarities in soil clay mineralogical composition within the profile suggested the inheritance of minerals from parent material, having no significant in-situ transformation under the prevailing conditions.